Prevalence and factors associated with serologically confirmed yaws infection among orang asli population in Hulu Terengganu, Malaysia - Hashim, Muhammad Aminuddin Che (2024)
Background: Yaws, caused by Treponema pallidum subspecies pertenue, is a major public health concern in tropical regions, affecting primarily children and marginalized communities, such as the Orang Asli in Hulu Terengganu, Malaysia. This reemerging neglected tropical disease poses a challenge to the global elimination efforts endorsed by the World Health Organization (WHO), highlighting the need for local epidemiological data to guide eradication strategies, thereby informing targeted interventions aligned with WHO's elimination goals. Objectives: To assess the prevalence and identify associated factors of serologically confirmed yaws infections among the Orang Asli population in Hulu Terengganu, Malaysia. Methodology: Using secondary data from the Terengganu State Health Department's Event Based Surveillance Database, a cross-sectional analysis was performed on 249 Orang Asli persons. The relationships between yaws infection and characteristics like age, gender, marital status, and comorbidities were investigated using Multiple Logistic Regression. Result: The study found that the prevalence of yaws infection in Hulu Terengganu, Malaysia is 17.3%, (95% CI: 0.128, 0.225) or 17,300 per 100,000 population in 2020. Age was the only significant predictor of yaws infection, with an adjusted odds ratio (AOR) of 0.977 (95% CI: 0.959, 0.995; p=0.012) per additional year, demonstrating that the risk of infection is decreasing with increment of age. No significant associations were found for gender, marital status, education level, and employment status with yaws infection. Discussion and Conclusion: The high prevalence of yaws infection among Orang Asli in Hulu Terengganu highlights the need for focused public health interventions, enhanced surveillance, and research efforts, particularly within indigenous and marginalized communities. The study’s findings support the need for implementation of targeted prevention and treatment programs towards the risky population in Malaysia.